2008
DOI: 10.1097/01.hnp.0000312659.21513.f9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Healing Touch on Stress Perception and Biological Correlates

Abstract: The objective of this pilot study was to investigate the effect of Healing Touch on state/trait anxiety and physiological measures of heart rate, blood pressure, muscle tension, skin conductance, and skin temperature in healthy adults. The study used a single group, repeated measures design with a nonprobability convenience sample of 30 subjects. Physiological data were collected for 10 minutes before intervention, during 30 minutes of Healing Touch treatment, and for 10 minutes posttreatment. During the cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 11 publications
1
32
0
3
Order By: Relevance
“…Para peneliti yang telah melakukan analisis perilaku manusia dan kesehatan telah mengembangkan teori-teori yang menjelaskan faktor-faktor dan interaksi di antara faktorfaktor yang memengaruhi kesehatan individu atau sekelompok individu, diantaranya adalah teori model kepercayaan kesehatan atau health belief model (HBM) (Maville & Huerta, 2008). Teori HBM merupakan salah satu teori yang paling sering digunakan dalam banyak studi tentang perilaku kesehatan (Painter, dkk., 2008).…”
Section: Pendahuluanunclassified
“…Para peneliti yang telah melakukan analisis perilaku manusia dan kesehatan telah mengembangkan teori-teori yang menjelaskan faktor-faktor dan interaksi di antara faktorfaktor yang memengaruhi kesehatan individu atau sekelompok individu, diantaranya adalah teori model kepercayaan kesehatan atau health belief model (HBM) (Maville & Huerta, 2008). Teori HBM merupakan salah satu teori yang paling sering digunakan dalam banyak studi tentang perilaku kesehatan (Painter, dkk., 2008).…”
Section: Pendahuluanunclassified
“…The effectiveness of TT in changing the parameters of vital signs such as blood pressure, heart and respiratory frequency has been verified in cancer patients (8) , critical patients (9) and in healthy individuals (10) . Among the most recent studies addressing TT, a clinical trial was conducted to investigate its effectiveness in improving sleep patterns, among other variables, and the authors found statistically significant results for latency (p=0.000), duration (p=0.008), habitual efficiency (p=0.021), disorders (0.000), daily sleepiness and sleep disorders during the day (0.002) (7) .…”
Section: Physiological Effectsmentioning
confidence: 99%
“…The studies addressing the effects of TT on anxiety and mood disorders have used questionnaires such as the Profile of Mood States (8) and State-Trait Anxiety Inventory (10) . The results, statistically significant for both (p=0.001 and p=0.003), indicate the improvement of symptoms.…”
Section: Psychological and Behavioral Effectsmentioning
confidence: 99%
“…7 The holistic nursing perspective is exhibited in the history of the profession in studying factors addressing the physical and also the psychological and spiritual aspects of a person, which influence the process of healing. 16 Within the holistic nursing paradigm, the concept of energy healing has been emerging, supported by advances in research from mind-body interactions and an increased consumer interest in CAM. 7 Interaction with energy is a fundamental concept in the practice of nursing, is recognized in the Nursing Interventions Classification Code, 17 and is a therapeutic component of selected nursing theories.…”
mentioning
confidence: 99%